4(x-1)-2(2x-8)+12 5,6-3(2-0,4х)-0,4(4х-1) 5(х-12)+6(х-10)-(х-1)

+865 голосов
2.0m просмотров

4(x-1)-2(2x-8)+12 5,6-3(2-0,4х)-0,4(4х-1) 5(х-12)+6(х-10)-(х-1)


Математика | 2.0m просмотров
+131

это 3 5(х-12)+6(х-10)-(х-1)

+128

это 2 5,6-3(2-0,4х)-0,4(4х-1)

+84

это 1 пример 4(x-1)-2(2x-8)+12

Дан 1 ответ
+165 голосов

Ответ:

Пошаговое объяснение:

4(x-1)-2(2x-8)+12 = 4x - 4 - 4x + 16 + 12 = 24

5,6-3(2-0,4х)-0,4(4х-1) = 5,6 - 6 + 1,2x - 1,6x + 0,4 = -0,4x

5(х-12)+6(х-10)-(х-1) = 5x - 60 + 6x - 60 - x + 1 = 10x - 119

(187k баллов)